Clang-clang! Beep-beep! : listen to the city - Burleigh, Robert; Giacobbe, Beppe (New York : Simon & Schuster Books for Young Readers, 2009)
From morning until night, a city is filled with such sounds as the roars and snores of a subway ride, the flutters and coos of pigeons, and the shouts and beeps of drivers in traffic.
"A Paula Wiseman book.".
Kirkus Review.
2.9
K-3
Keywords: City and town life -- Fiction; Noise -- Juvenile fiction; Sound -- Juvenile fiction; City and town life -- Fiction; Noise -- Fiction; Sound -- Fiction; Stories in rhyme; City and town life -- Fiction; Noise -- Fiction; Sound -- Fiction; Stories in rhyme